"IT IS HIS IMAGE WITH PULQUE": DRINKS, GIFTS, AND POLITICAL NETWORKING IN CLASSIC MAYA TEXTS AND IMAGES. Issue 1 (3rd June 2016) - Tokovinine, Alexandre
Abstract: Despite a widespread notion that feasting played a major role in the workings of Classic Maya polities, the very concept of feasting in the context of its textual and visual representations remains poorly defined and understood. The present paper reviews the ancient narratives in order to present a more nuanced interpretation of the consumption and display of exquisite food and drinks at the courts of Maya lords and nobles. It also considers some tangible evidence of the sociopolitical networks created through feasting by looking at the spatial distributions of signed serving vessels which changed hands as gifts.